U.S.-Cuban Agricultural Trade: Present Realities and Future Prospects - William A. Messina, Jr. (EDIS, 2003)
Testimony presented before the U.S. Senate Finance Committee by William A. Messina, Jr. on September 4, 2003. This is EDIS document FE438, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published November 2003.